Viskositas Darah dan Plasma Pada Talasemia Mayor - Korwa, Daniela Dirgantari; Timan , Ina Susianti; Sinsanta, Sinsanta; Sari , Dominica Pita (Universitas Kristen Krida Wacana, 2025)
Background: viscosity or viscosity is a physical property that characterizes the resistance to a fluid flow. Fluids have both Newtonian and non-Newtonian properties. Viscosity is divided into blood and plasma viscosity. One of the pathological conditions that can affect blood and plasma viscosity is thalassemia. Thalassemia is a disorder of imperfect globin chain formation resulting in imperfect erythrocyte formation. In 2021, 10,670 cases of thalassemia were reported. The viscosity value in the thalassemia group currently does not have a definite value. Objective: this study involved 57 people who were divided into a control group and a thalassemia group. The control group samples will undergo 5 cc of venous blood collection for a complete hematology and viscosity examination using a digital neo microcapillary device (NMD), but the thalassemia group samples will be taken from the remaining blood for hematology examination before transfusion and viscosity examination. Data analysis was carried out univariately and bivariately using t – test and Mann Whitney test with p < 0.05.Results: it was found that the thalassemia group had a blood viscosity value of 5.67 ± 1.72 cP and plasma viscosity of 3.29 ± 1.2 cP Conclusion: blood viscosity and plasma viscosity in the thalassemia group were higher compared to controls